New data on distribution of Chamaesphecia efetovi O. Gorbunov, 2019, in the Crimea (Lepidoptera: Sesiidae) - K. A. Efetov; O. G. Gorbunov (SHILAP)
Chamaesphecia efetovi O. Gorbunov was described in 2019 from the Crimea, Volgograd Region and Stavropol Territory (Russia). In the Crimea, this species was mentioned from 15 localities. In 2020, the authors continued studying the range of this species in the Crimea and found 24 additional localities. Ch. efetovi is widely distributed in the Crimea in Plain region, Kerch Peninsula and in some localities of Mountain region. The peculiarities of the biology of the species are discussed. Ch. efetovi is also known from Romania, Bulgaria and Serbia. It is assumed that this species can also be distributed in adjacent territories: Moldova, Ukraine, Turkey, and (in addition to Bulgaria and Serbia) in other countries of the Balkan Peninsula. The confirmation of this requires further research.